2017
DOI: 10.1021/acschemneuro.6b00451
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipid Butyl Ester Diacetate Does Not Affect Macrophage Polarization but Enhances Astrocytic Glial Fibrillary Acidic Protein Expression at Micromolar Concentrations in Vitro

Abstract: Peritoneal macrophages (PMACs) and spinal cord astrocytes were exposed to varying concentrations of soluble sophorolipid butyl ester diacetate (SLBEDA) in vitro. Macrophages and astrocytes demonstrated no decrease in viability in response to SLBEDA. Studying pro-and antiinflammatory genes, PMACs did not show a shift toward a pro-inflammatory phenotype. However, at higher concentrations (3 and 30 μM), astrocytes showed an increase in their expression of glial acidic fibrillary protein. This novel category of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Quantitative polymerase chain reaction was conducted per previous lab protocols (39). The primers used are listed in Table 1.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
“…Quantitative polymerase chain reaction was conducted per previous lab protocols (39). The primers used are listed in Table 1.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
“…For example, one study recently concluded that 30 μM B did not affect LPSinduced mouse peritoneal macrophage viability, consistent with our results for this SL-ester. 45 Other studies have found significant cytotoxic effects of L on a variety of cell types, 61 including normal colonic epithelial cells and various colorectal cancer cell lines at 0.03 or 0.1 μM, respectively. Finally, Fu and colleagues found that L had greater toxicity than M when tested on human pancreatic carcinoma cells, 26 Beyond confirming some of these general viability trends, to our knowledge this study is the first to examine the impact of a range of different SL formulations, concentrations, and time points on macrophage viability.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, the immunomodulatory properties of L and B on the macrophage phenotype have been documented only in the contexts of sepsis 29,47,67 and spinal cord injury. 45 Bluth and colleagues showed that treatment with natural SLs (L makes up the highest proportion 23 ) significantly reduced nitric oxide production from LPS-activated RAW 264.7 cells, consistent with the reduction of pro-inflammatory markers IL-6 and TNF-α noted with L herein. 29 In contrast, the same authors observed an increase in IL-1β and TNF-α but no change in IL-6 gene expression in an LPS-activated rat alveolar macrophage cell line exposed to SLs for 36 h. Moreover, Ziemba and colleagues found that the treatment of peritoneal macrophages with B (3 nM to 30 μM for 24 h) did not affect the gene expression of either M1 markers (nitric oxide synthase and IL-12p40) or M2 markers (arginase-1 and IL-10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations